Effects of natural disasters on agricultural production activities in the Cambodia-Laos-Vietnam development triangle area: case studies of Ratanakiri (Cambodia), Attapeu (Laos) and Kon Tum (Vietnam) provinces - Nguyen, Tuan Anh (2016)
The Cambodia-Laos-Vietnam Development Triangle (CLVDT) area is strategically placed vis-à-vis the economic, social and ecological-environmental aspects of the three countries involved. The agricultural sector has played an important role in contributing to economic growth, ensuring food security, and creating jobs and income for the local people. However, the sector is also one of the worst affected by natural disasters such as floods, flash floods and drought. Since 2001, disasters have occurred in the three provinces of Kon Tum (in Vietnam), Ratanakiri (in Cambodia) and Attapeu (in Laos) every year. While natural disasters have both negative and positive effects on agricultural production-related activities, outcomes are mostly negative. Natural disasters have serious consequences on agricultural production (such as field land, forest land and fishing area), its output, the agricultural infrastructure system, in general, as well as farmer’s lives. Various stakeholders are involved in responding to the negative impacts of natural disasters, including central and local governments, the local population, and non-governmental organisations. This paper highlights the significance of indigenous knowledge in adapting to natural disasters in the CLVDT area, as well as the main challenges and recommendations for adapting to and mitigating the negative impacts of natural disasters.